Traveling with pomegranates [compact disc, unabridged] : a mother daughter story - Kidd, Sue Monk (Penguin Audio, 2009)
Sue Monk Kidd, author of The Secret Life of Bees, and Ann Taylor Kidd, her daughter, co-author this personal narrative about their experience together while traveling Europe. Listen as the two women learn a great deal about one another and strengthen the mother and daughter bond, as they visit the world's most beautiful spots.